Evaluating Teaching Effectiveness through Student Reflections: An Inquiry into English Language Instruction - Misnawati Misnawati; Zul Astri; Saidna Zulfiqar bin Tahir; Reski Pilu; Alwi Sibali (PT. Global Research Collaboration, 2025)
This study investigated student perceptions of teaching effectiveness in an English for Specific Purposes (ESP) course using a mixed methods approach. The research involved 65 first-semester undergraduate students from seven academic disciplines at a private University in Indonesia. Data were collected through an end-of-semester evaluation form consisting of Likert-scale items and open-ended questions. Quantitative findings indicated that students perceived the course as most effective in enhancing their reading and vocabulary skills. Other language areas—speaking, writing, listening, and grammar—also received favorable ratings, although with more variability. Thematic analysis of qualitative responses revealed that students attributed their progress to specific instructional strategies such as text-based reading tasks, vocabulary drills, and interactive speaking activities. They also highlighted grammar instruction as helpful for improving sentence construction and clarity. Suggestions for improvement included increased integration of technology, hybrid learning modes, and more personalized support. Overall, the study demonstrated that student evaluations can serve as assessment tools and reflective instruments to inform and enhance teaching practice. The study offered a nuanced perspective on how ESP instructional strategies influenced student learning by combining numerical and narrative data. These findings support using student feedback as a dynamic resource for pedagogical development.